4x^4+3x^2-1=0

Simple and best practice solution for 4x^4+3x^2-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x^4+3x^2-1=0 equation:


Simplifying
4x4 + 3x2 + -1 = 0

Reorder the terms:
-1 + 3x2 + 4x4 = 0

Solving
-1 + 3x2 + 4x4 = 0

Solving for variable 'x'.

Factor a trinomial.
(-1 + -1x2)(1 + -4x2) = 0

Factor a difference between two squares.
(-1 + -1x2)((1 + 2x)(1 + -2x)) = 0

Subproblem 1

Set the factor '(-1 + -1x2)' equal to zero and attempt to solve: Simplifying -1 + -1x2 = 0 Solving -1 + -1x2 = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x2 = 0 + 1 -1x2 = 0 + 1 Combine like terms: 0 + 1 = 1 -1x2 = 1 Divide each side by '-1'. x2 = -1 Simplifying x2 = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5

Subproblem 3

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Solution

x = {-0.5, 0.5}

You can always share this solution

See similar equations:

| kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 | | 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 | | 3x^2+12x=180 | | 4x^2+13x-75=0 | | 4x^2+13-75=0 | | 3x^2+10x-88=0 | | 2v^2-4v+52= | | v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 | | 5x^2=13x+6 | | x^2+10x+25=0 | | X^2+4x+4=0 | | x^2+6x+9=0 | | -4x=2x^2-6 | | -x=2x^2-6 | | -2x=3x^2-1 | | -9x=2x^2-5 | | x^2-5x-6=0 | | x^2-x-12=0 | | 3x^2+5x-13=11-9x | | 5x^3-5x=0 | | 16x^2+2x-3=0 | | 4x^2-25=0 | | x^2-19x=0 | | x^2-x+18=0 | | 13x^2-11x=0 | | 7x^2+4x-15=49-44x | | 3x^3+9x^2+6x=0 | | x^2-3x-18=0 | | x^2-63x+60=0 | | 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 | | 8x^3+10xy+6x^2y^5=0 | | 2X(X^2-4X+7)= | | 2x^2-5x-5=0 | | 2x^2-38x=7x^2-3x-24 | | 9p^2+18p=10 |

Equations solver categories